Estudo epidemiológico dos achados incidentais em seios maxilares, em amostra populacional de São Luís do Maranhão, por meio da tomografia computadorizada de feixe cônico - Calixto, Caio Tupinambá (2019)
The maxillary sinus, called Highmore's Den, is an air cavity located inside the maxilla, extending to the zygomatic process of the maxilla. Understanding the anatomy of the maxillary sinus is of fundamental importance when imagining the Maxillofacial Complex, as well as recognizing the anatomical variations, considered within the normal range, allows the identification of possible disorders, which may be present. In this air cavity, in particular those called asymptomatic, and even considered as incidental findings. Cone-Beam Computed Tomography is a diagnostic imaging method, which is essential for the radiographic interpretation of maxillary sinus morphology, as well as its anatomical variations and the alterations that affect it. Given the importance of knowledge pertaining to the anatomy of the maxillary sinuses, the aim of this study was to analyze, by means of Cone-Beam Computed Tomography, the anatomical variations and the considered incidental affections that affected the maxillary sinuses, relating them to data. Population in a sample of São Luís do Maranhão, oriented to the realization of this imaginative resource, facing the different clinical demands, according to the request of the Dental Specialties. We analyzed 400 Cone-Beam Computed Tomography images, belonging to an Image Bank, by a Dental Radiologist observer, who received previous training, for a better observation of the tomographic images, taking into consideration the anatomical variations (sinus partition). And bone outgrowth) and conditions (generalized mucosal thickening, periapical mucositis, sinus polyp, acute rhinosinusitis, chronic rhinosinusitis, fungal rhinosinusitis, and antral pseudocyst), all of which were identified and interpreted. All data were analyzed descriptively and through correlations, taking into account the demographic data (gender and chronological age) referring to the patients. Fischer's exact and Chi-square tests were used to verify the statistical association between demographic data and the highest incidence of anatomical variation in the sample of this study, as well as with the most prevalent condition in the maxillary sinuses analyzed. Four hundred CBCTs were evaluated. Of the 400 patients, 251 (62.75%) were female and 149 (37.25%) male, with chronological age between 10 and 91 years. Among the studied anatomical variations (sinus partition and bone excrescence), the highest incidence was sinus partition, ie present in 278 sinus cavities, in 34.62% of the total sample. When identifying and interpreting the aforementioned sinus disorders present on tomographic images, periapical mucositis was the most prevalent, ie present in 231 maxillary sinuses (28.87%) of the total sample. We found that there was no statistical association between patient's gender and tomographic finding, either sinus partition (anatomical variation) or periapical mucositis (sinus disorder), since the values of "p" were greater than 0.05. Thus, there is no higher prevalence of any of the above incidental findings, in either sex, which is statistically significant. CBCT images can be considered as preferred for the imaging interpretation of the maxillary sinuses, since it allows the identification of the so-called morphological variations of the respective bone architecture, as well as the physiological and or pathological changes present in these paranasal sinuses; contributing to the professionals of the different Dental Specialties, when diagnosing and planning the treatment to be performed, in front of patients with different degrees of clinical severity.